“Comparative Study of 2-Dimensional and 3-Dimensional Analysis of a Deep Excavation in Situ Measurements” - Prasant S. Lanjewar, Damodar Ghosh (Mathematical Statistician and Engineering Applications, 2022)
The process of designing for deep excavations is a difficult one that requires taking into account a broad variety of aspects. These factors include the processes that are involved in developing the excavation as well as the physical characteristics of the soil. The use of finite element analysis can be beneficial to the design of deep excavations; however, it must be carried out with caution in order to guarantee that an acceptable quantity of information is included in the model. A diaphragm wall, a jet grout panel, and three layers of struts were used to provide support for the excavation. When the lower rigidity of the diaphragm wall owing to cracking was taken into consideration, evaluation and comparison with in-situ measurements indicated that the best agreement with the data occurred.